2018
DOI: 10.1051/0004-6361/201732317
|View full text |Cite
|
Sign up to set email alerts
|

The shape of convective core overshooting from gravity-mode period spacings

Abstract: Context. The evolution of stars born with a convective core is highly dependent on the efficiency and extent of near core mixing processes, which effectively increases both the core mass and main-sequence lifetime. These mixing processes remain poorly constrained and therefore result in large uncertainties in the stellar structure and evolution models of such stars. Aims. We investigate to what extent gravity-mode period spacings in slowly pulsating B-type stars observed by the Kepler mission can be used to co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
126
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(131 citation statements)
references
References 73 publications
(91 reference statements)
5
126
0
Order By: Relevance
“…Additionally, the chemical mixing alters ∇ µ just outside of the core according to the chosen prescription. Recent asteroseismic modelling by Moravveji et al (2015Moravveji et al ( , 2016 has shown that a diffusive exponential overshooting better reproduces observed period-spacing patterns of B-type stars of ∼ 3M compared to a diffusive step overshooting implementation -see also Pedersen et al (2018) for the capacity of g modes to distinguish these two from mode trapping. Here, we use diffusive exponential overshooting in our grid, taking the values shown in Table 1.…”
Section: Convection and Overshootingmentioning
confidence: 95%
“…Additionally, the chemical mixing alters ∇ µ just outside of the core according to the chosen prescription. Recent asteroseismic modelling by Moravveji et al (2015Moravveji et al ( , 2016 has shown that a diffusive exponential overshooting better reproduces observed period-spacing patterns of B-type stars of ∼ 3M compared to a diffusive step overshooting implementation -see also Pedersen et al (2018) for the capacity of g modes to distinguish these two from mode trapping. Here, we use diffusive exponential overshooting in our grid, taking the values shown in Table 1.…”
Section: Convection and Overshootingmentioning
confidence: 95%
“…This is predicated on the non-zero inertia of convective bubbles at a convective boundary causing them to overshoot into a radiative layer. In massive stars, the overshooting of the convective core (also known as convective-boundary mixing) entrains hydrogen from the envelope into the core resulting in a longer main sequence lifetime and a larger helium core mass (Pedersen et al, 2018;Michielsen et al, 2019). This has a direct impact on the characteristic g-mode period, 0 , of main-sequence stars with convective cores (Mombarg et al, 2019).…”
Section: Interior Mixingmentioning
confidence: 99%
“…Typically, these two prescriptions in the shape of convective core overshooting are referred to as α ov and f ov , respectively, in the literature and differ approximately by a factor of 10-12 (Moravveji et al, 2015). However, it is only recently that asteroseismology has demonstrated the potential to discriminate them in observations using g-mode period spacing patterns (Moravveji et al, 2015(Moravveji et al, , 2016Pedersen et al, 2018). Moreover, there is considerable ongoing work using 3D hydrodynamical simulations (Augustson and Mathis, 2019) and g-mode pulsations to probe the temperature gradient within an overshooting layer and ascertain if it is adiabatic, radiative, or intermediate between the two (Michielsen et al, 2019).…”
Section: Interior Mixingmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference to Equation 1 is that the decay in the mixing velocities result a smoothly varying composition rather than a step in the mean-molecular weight profile. We refer the reader to Pedersen et al (2018) for a recent summary of the possible formulations of chemical mixing at convective boundaries (Herwig et al 2007;Rogers & McElwaine 2017).…”
Section: Numerical Implementation Of Overshootmentioning
confidence: 99%